A construction of integrated vertex operator in the pure spinor sigma-model in AdS(5) x S-5 - Chandia, Osvaldo; Mikhailov, Andrei [UNESP]; Vallilo, Brenno C. (Springer, 2013)
Vertex operators in string theory me in two varieties: integrated and unintegrated. Understanding both types is important for the calculation of the string theory amplitudes. The relation between them is a descent procedure typically involving the b-ghost. In the pure spinor formalism vertex operators can be identified as cohomology classes of an infinite-dimensional Lie superalgebra formed by covariant derivatives. We show that in this language the construction of the integrated vertex from an unintegrated vertex is very straightforward, and amounts to the evaluation of the cocycle on the generalized Lax currents.
Keywords: Superspaces; NoN-Commutative Geometry; Conformal Field Models in String Theory; AdS-CFT Correspondence